Implementation of the Code of Ethics for State Civil Apparatus in the Muara Bangkahulu Sub-District of Bengkulu City - Dwika Edo Rahmadani; Achmad Aminuddin; Nourfarozi Agus (International Journal of Scientific Multidisciplinary Research, 2024)
The aim of this study is to understand how the Code of Ethics for State Civil Servants is regulated and implemented in the Bengkulu City Government. It aligns with one of the areas of change outlined in the 2020-2024 bureaucratic reform roadmap, which focuses on improving the mindset of Indonesian state civil servants. The research method used is descriptive qualitative, which involves case studies and in-depth research within a specific unit. Data collection methods include observation, interviews, and document analysis. The findings indicate that several factors hinder the effective implementation of the Code of Ethics among State Civil Servants in Bengkulu City. These factors include a lack of understanding of the regulations, insufficient recognition for exemplary employees, leniency in enforcing disciplinary sanctions, declining employee discipline, and inadequate supervision